WOAPR: an affinity propagation based clustering and optimal path selection for time‐critical wireless sensor networks. Issue 2 (1st March 2019) - Sakthidasan, Krishnan; Vasudevan, Natarajan; Kumara Guru Diderot, Paramesvarane; Kadhiravan, Chellakkutti
Abstract : Wireless sensor networks (WSNs) spread their returns to every field having the requirement of continuous monitoring. Clustering is an important mechanism in WSN for minimum energy consumption and better network performance. In these networks, optimal paths need to be determined for efficient flow of data. The power efficiency and quality of service are the two most essential aspects looked‐for to realise the network. However, this hypothesis has been a changing characteristic based on the innovative applications. Consequently, the quality‐of‐service aspect is gaining much significance than the efficient power design of the sensor network. This study proposes a clustering‐based routing protocol for time‐critical WSN named as whale optimised affinity propagation‐based routing protocol. This protocol reduces energy consumption and improves energy efficiency through clustering and routing algorithms. The performance of the proposed protocol is evaluated using various metrics and the proposed approach shows significant improvement over the existing approaches.